Do 12‐Month‐Old Infants Trust a Competent Adult?. (20th February 2013) - Stenberg, Gunilla
<x xml:space="preserve">Abstract</x> Why infants prefer to look at and use information provided by some informants over others was examined in four experiments. In each experiment, 52 12‐month‐old infants participated. In Experiment 1, a familiar expert and a familiar nonexpert and in Experiment 2, a novel expert and a novel nonexpert presented an ambiguous object and provided positive information. In both experiments, the infants preferred to look at the expert and regulated their behavior more in accordance with positive information provided by the expert, regardless of she was novel or more familiar. In Experiment 3, a familiar expert and a familiar nonexpert and in Experiment 4, a novel expert and a novel nonexpert presented an ambiguous object and provided negative information. In both experiments, the infants looked more at the expert and regulated their behavior more in accordance with negative information provided by the expert, regardless of she was novel or more familiar. The results support an expertise perspective of infant behavior in social‐referencing situations.